ChemInform Abstract: Copper‐Catalyzed Esterification of Alkylbenzenes with Cyclic Ethers and Cycloalkanes via C(sp3)—H Activation Following Cross‐Dehydrogenative Coupling. Issue 48 (2nd December 2014) - Rout, Saroj Kumar; Guin, Srimanta; Ali, Wajid; Gogoi, Anupal; Patel, Bhisma K.
Abstract The synthesis of α‐acyloxy ethers from simple solvents as reactants is reported.